Determination of Zakat Nisab for Agricultural Products According to Today’s Units of Measurement - Abdulmelik Kutluay (Darulfunun Ilahiyat)
A condition required for zakat obligation (an obligatory alms-giving in Islam) is that the goods subject to zakat should reach a certain amount (nisab). The nisab of agricultural products, which are among the zakat goods, was determined by the old volume measurement units. The absence of measurement units in the time of the Prophet and the determination of the amount of agricultural products in weight units rather than volume have made it necessary to redetermine the nisab in the present time. In this study, the nisab for different agricultural products was determined according to today’s measurement units. In this context, the equivalents of the old volume measurement units are determined in the modern weight measurement units. The conflict between the Hanafis and other scholars on the issue is mentioned, and the nisab is determined according to the two views. In addition, based on the view that the nisab shall be determined by using the palm, we made some measurements and presented the results. As the density of agricultural products differ, separate measurements were made for each product. The opinions and methods proposed for determining the nisab were evaluated. Further, the nisab of agricultural products that cannot be measured using volume measurement units is discussed, and the results are presented.